2015
DOI: 10.1152/ajpregu.00379.2014
|View full text |Cite
|
Sign up to set email alerts
|

Influence of gonadal hormones on the behavioral effects of intermittent hypoxia in mice

Abstract: Obstructive sleep apnea (OSA) is characterized by repetitive upper airway obstruction resulting in cyclic intermittent hypoxia (IH) during sleep in affected individuals. OSA occurs more frequently in postmenopausal than premenopausal women and the severity of OSA increases after menopause. Gonadal hormones can influence brain and behavior; testosterone and estrogens in particular can enhance spatial learning and memory. We hypothesized that estrogens may protect mice from IH-induced hippocampal morphological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
4
7
0
Order By: Relevance
“…Future experiments with DHT treatment may require a longer habituation phase to reduce the novelty aspect. Overall, these findings are consistent with literature demonstrating that both testosterone and estrogens are protective in the CNS and facilitate memory, while DHT can contribute to damaging processes on occasion (Aubrecht et al, 2014; Beer et al, 2006; Bimonte-Nelson et al, 2003; Frye et al, 2008; Osborne et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Future experiments with DHT treatment may require a longer habituation phase to reduce the novelty aspect. Overall, these findings are consistent with literature demonstrating that both testosterone and estrogens are protective in the CNS and facilitate memory, while DHT can contribute to damaging processes on occasion (Aubrecht et al, 2014; Beer et al, 2006; Bimonte-Nelson et al, 2003; Frye et al, 2008; Osborne et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Whereas estrogens have been well established as protective against cardiovascular (dos Santos et al, 2014; Hinojosa-Laborde and Mifflin, 2005) and neurodegenerative disorders (Aubrecht et al, 2014; Gillies et al, 2004), the role of androgens is less defined (Aubrecht et al, 2014; Barron and Pike, 2012; Grimm et al, 2016; Holmes et al, 2013; Lau et al, 2014). Both estrogens and androgens can mediate rapid and long-term effects within the CNS, such as calcium signaling, increasing spine density within hippocampal regions or altering DNA transcription (Acaz-Fonseca et al, 2016; Cunningham et al, 2007; Handa et al, 2008; Jacome et al, 2016; Mahmoud et al, 2016; McEwen and Milner, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our results demonstrated that reflex apneic responses and LVCF responses to stimulants in OVX + IH rats were significantly greater than those in all other groups ( Figures 2 , 4 ), suggesting that ovarian hormones exert a protective effect. This concept is further supported by previous studies showing that intact female animals are protected from IH-induced hypertension ( Hinojosa-Laborde and Mifflin, 2005 ) and impairment of spatial learning and memory ( Aubrecht et al, 2015 ); however, OVX removes this protection. The exact mechanism underlying the potentiating effect of OVX combined with IH exposure on LVCF sensitivity is unknown.…”
Section: Discussionsupporting
confidence: 66%
“…Age and sex are two factors implicated in the prevalence of the disease, with men having two- to threefold greater risk for OSA compared to women, and for people older than 60 years having an AHI >15 is approximately 1.7-fold higher than middle-aged persons 6,7. The reason for the sex risk difference was initially explained by the protective role of progesterone and estrogens,8 as well as exposure to other risk factors in men such as fat deposition, smoking, and alcohol intake. The most probable explanation is that there are clear sex and age differences in the upper airway shape, genioglossal muscle activity, and craniofacial morphology, accounting for a higher male risk 9.…”
Section: Introductionmentioning
confidence: 99%